Elevated Pressure Increases Ca2+ Influx Through AMPA Receptors in Select Populations of Retinal Ganglion Cells - Wen, Xiangyi; Cahill, Asia L.; Barta, Cody; Thoreson, Wallace B.; Nawy, Scott (Frontiers in Cellular Neuroscience, 2018)
The predominate type of AMPA receptor expressed in the CNS is impermeable to Ca2+ (CI-AMPAR). However, some AMPA receptors are permeable to Ca2+ (CP-AMPAR) and play important roles in development, plasticity and disease. In the retina, ganglion cells (RGCs) are targets of disease including glaucoma and diabetic retinopathy, but there are many types of RGCs and not all types are targeted equally. In the present study, we sought to determine if there are differences in expression of AMPARs amongst RGC subtypes, and if these differences might contribute to differential vulnerability in a model of stress. Using cultured RGCs we first show that acute exposure to elevated pressure increased expression of Ca2+-permeable AMPA receptors (CP-AMPARs) in some, but not all classes of RGCs. When RGCs were sampled without regard to subtype, AMPA currents, measured using patch clamp recording, were blocked by the CP-AMPAR blocker PhTX-74 to a greater extent in pressure-treated RGCs vs. control. Furthermore, imaging experiments revealed an increase in Ca2+ influx during AMPA application in pressure-treated RGCs. However, examination of specific RGC subtypes using reporter lines revealed striking differences in both baseline AMPAR composition and modulation of this baseline composition by stress. Notably, ON alpha RGCs identified using the Opn4 mouse line and immunohistochemistry, had low expression of CP-AMPARs. Conversely, an ON-OFF direction selective RGC and putative OFF alpha RGC each expressed high levels of CP-AMPARs. These differences between RGC subtypes were also observed in RGCs from whole retina. Elevated pressure further lowered expression of CP-AMPARs in ON alpha RGCs, but raised expression in ON-OFF and OFF RGCs. Changes in CP-AMPAR expression following challenge with elevated pressure were correlated with RGC survival: ON alpha RGCs were unaffected by application of pressure, while the number of putative OFF alpha RGCs declined by approximately 50% following challenge with pressure. Differences in expression of CP-AMPARs between RGC subtypes may form the underpinnings for subtype-specific synaptic plasticity. Furthermore, the differential responses of these RGC subtypes to elevated pressure may contribute to the reported resistance of ON alpha, and susceptibility of OFF and ON-OFF RGCs to injury in models of glaucoma.